2007
DOI: 10.1016/j.yexmp.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A focused salivary gland infection with attenuated MCMV: An animal model with prevention of pathology associated with systemic MCMV infection

Abstract: While the salivary gland has been recognized as an important effector site of the common mucosal immune system, a useful model for studying anti-viral salivary gland immune responses in vivo and for exploring the role of the salivary gland within the common mucosal system has been lacking. Murine cytomegalovirus (MCMV) is a beta-herpesvirus that displays a strong tropism for the salivary gland and produces significant morbidity in susceptible mice when introduced by intraperitoneal (i.p.) inoculation. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 33 publications
1
41
1
Order By: Relevance
“…Nevertheless, since mouse CMV (mCMV) has many features in common with hCMV, and mCMV infection of mice resembles its human counterpart with respect to pathogenesis, the mouse animal model ( in vitro and in vivo ) has been extensively used to understand the pathogenesis of acute, latent, and recurrent infections (e.g. Reynolds et al, 1993; Lagenaur et al, 1994; Schmader et al, 1995; Krmpotic et al, 2003; Melnick et al, 2006; Pilgrim et al, 2007; Jaskoll et al, 2008a, 2008b; Bai et al, 2008; Kasman et al, 2009). As with humans, the SMG is the major target organ for mCMV replication in the infected mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, since mouse CMV (mCMV) has many features in common with hCMV, and mCMV infection of mice resembles its human counterpart with respect to pathogenesis, the mouse animal model ( in vitro and in vivo ) has been extensively used to understand the pathogenesis of acute, latent, and recurrent infections (e.g. Reynolds et al, 1993; Lagenaur et al, 1994; Schmader et al, 1995; Krmpotic et al, 2003; Melnick et al, 2006; Pilgrim et al, 2007; Jaskoll et al, 2008a, 2008b; Bai et al, 2008; Kasman et al, 2009). As with humans, the SMG is the major target organ for mCMV replication in the infected mouse.…”
Section: Introductionmentioning
confidence: 99%
“…We previously described a model of a focused salivary gland infection, which we used to investigate the hypothesis that the salivary gland acts as a mucosal inductive site, as well as its known function as an effector site in oral mucosal immunity (8, 9). We demonstrated that intraglandular inoculation with tissue cultureā€derived murine cytomegalovirus (tcMCMV), which is attenuated with respect to its ability to infect systemic tissues, limited infection to the salivary gland without high viral titers and pathology in other organs and stimulated a local host immune response (8, 9).…”
mentioning
confidence: 99%
“…We previously described a model of a focused salivary gland infection, which we used to investigate the hypothesis that the salivary gland acts as a mucosal inductive site, as well as its known function as an effector site in oral mucosal immunity (8, 9). We demonstrated that intraglandular inoculation with tissue cultureā€derived murine cytomegalovirus (tcMCMV), which is attenuated with respect to its ability to infect systemic tissues, limited infection to the salivary gland without high viral titers and pathology in other organs and stimulated a local host immune response (8, 9). This immunization protocol also induced salivary gland ectopic follicles that displayed both functional and phenotypic characteristics of mucosal inductive site germinal centers (GCs) including cognate interactions of B and T cells with follicular dendritic cells, proliferating cells, class switching, plasma cell differentiation, and protection against a lethal systemic challenge with MCMV (8, 9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because we demonstrated that both intraglandular inoculation (5, 6) and retrograde perfusion of the submandibular salivary gland (7) with tcMCMV generated MCMVā€specific Tā€cell immunity, we evaluated the T h 1/T h 2/T h 17 immune responses after both tcMCMV inoculation and a lethal MCMV challenge. BALB/cByJ mice were inoculated with saline or 10 5 PFU/mouse tcMCMV via retrograde perfusion of the submandibular gland.…”
Section: Resultsmentioning
confidence: 99%